MANAJEMEN MUTU MADRASAH BERBASIS KEARIFAN LOKAL DALAM PERSPEKTIF JOSEP M. JURAN - Kamila Ida Suwarno (Universitas Nurul Jadid, 2020)
The quality of a product is one of the most important factors in increasing the competitiveness of a product. Total Quality Management is an approach used in running a business to maximize the competitiveness of an organization through continuous improvement of its services, products, processes and environment. Total Quality Management according to Josep M. Juran Quality is the suitability of a product use (Fitness For Use) which is to meet customer needs and satisfaction. Josep is often referred to as